2001
DOI: 10.2355/isijinternational.41.239
|View full text |Cite
|
Sign up to set email alerts
|

Nitride Capacities of CaO-Al2O3-CaF2 Melts at 1773K.

Abstract: The nitrogen solubility of CaO-Al 2 O 3 -CaF 2 was studied at 1 773 K. It was found that nitride capacity increased with increasing CaO content for a given CaF 2 /Al 2 O 3 ratio, decreased with increasing Al 2 O 3 content for a given CaO/CaF 2 ratio, and increases with increasing CaF 2 content when the CaO/Al 2 O 3 molar ratio was less than about 2, but became unaffected by CaF 2 content when the ratio exceeded about 2. These observations were interpreted that CaO depolymerized the Al 2 O 3 network, allowing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The presence of various nitrides in the slag (Table 2) indicates that a soda‐rich slag possesses considerable nitride capacity. This is in conformity with the observations of a recent study [5] on the nitride capacity of basic slags.…”
Section: Resultssupporting
confidence: 93%
“…The presence of various nitrides in the slag (Table 2) indicates that a soda‐rich slag possesses considerable nitride capacity. This is in conformity with the observations of a recent study [5] on the nitride capacity of basic slags.…”
Section: Resultssupporting
confidence: 93%
“…A fundamental understanding of the thermodynamics and kinetics of nitrogen dissolution in slags allows the design of optimum slag compositions and process parameters to achieve the required levels of nitrogen in molten steels. While many studies on the thermodynamics of nitrogen dissolution in slags using a gas-slag equilibration technique have been done [1][2][3][4][5][6], there are only a limited number of studies available on the kinetics as far as the authors knowledge. In particular, nitrogen dissolution on the surface of the slag and the effects of additives such as Al 2 O 3 are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic evaluations have shown that nitrogen in molten slag can dissolve as N 3− (free nitride), N 0 (bridged nitride), or N − (non-bridged nitride) and expressed by the following [1][2][3][4][5][6]. Where O 2− is the free oxygen ion, O − is the non-bridged oxygen, and O 0 is the bridged oxygen.…”
Section: Introductionmentioning
confidence: 99%